Sosialisasi Desain Kemasan dan Label Produk Sabun Cuci Piring pada Dasawisma Anggrek Bulan Desa Pandau Jaya - Elida Gultom; Nova Syafrina; Lamin Lamin; Jeli Nata Liyas; Siti Syahsudarmi (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
This community service was carried out at Dasawisma Anggrek Bulan in Pandau Jaya Village, Siak Hulu District, Kampar Regency, Riau Province. This activity was held on Sunday 09 June 2024 with the theme Socialization of Packaging and Label Design for Dish Soap Products at Mompreneur Wisma Anggrek Bulan, Pandau Jaya Village. Packaging and labels are one of the important factors in product marketing. Apart from protecting the product to prevent damage, packaging is also a promotional tool to attract consumer interest. This service activity was carried out with the aim of increasing the knowledge of Dasawisma Anggrek Bulan mompreneurs regarding branding. The method of implementing this service is carried out in two ways, namely the lecture method and practice. It is hoped that the results of this community service activity will increase the understanding and ability of mompreneur members of Dasawisma Anggrek Bulan in making product packaging and labels so that they are useful and have a positive impact on the business being developed.